Health-Related Quality-of-Life in a cohort undergoing cholecystectomy. Issue 1 (March 2015) - Rydbeck, Daniel; Anesten, Bengt; Barje, Therese; Hajnal, Peter; Österberg, Johanna; Sandblom, Gabriel
Abstract Introduction Patient-related outcome measures are crucial when assessing outcome from surgical intervention registers. The aim of this study was to analyse what factors affect Health-Related Quality of Life (HRQoL) in patients undergoing cholecystectomy, and to assess the feasibility of SF-36 as a HRQoL instrument in a patient register. Methods The SF-36 questionnaire was distributed to patients preoperatively and 6–9 months after surgery. The outcome of patients who had undergone planned surgery between January 1, 2010 and June 30, 2011 at six units, with response rates of at least 100 per year, formed the basis for the present study. Expected outcome from a background population was determined from a Swedish cohort assembled previously. Results Altogether 919 patients (646 women, 273 men) at the six units answered the questionnaire. Mean age was 52 years, standard deviation 15 years. Preoperatively, the surgery cohort rated lower on all subscales of the SF-36 than the age- and gender-matched background population. Postoperatively, they did not rate lower in any of the subscales. High age was associated with a significantly lower increase in bodily pain and Physical Component Summary (both p < 0.05). Open surgery was associated with a significantly lower increase in the Physical Component Summary (p < 0.05). Discussion Regardless of indication for surgery, high age is associated with less benefit from surgery according to this questionnaire study. SF-36 is appropriate for measuring the impact of gallstone surgery on HRQoL.